2024
DOI: 10.3390/coatings14020209
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a Mathematical Model of Product Color Design Based on Data Mining: Case Study of a Thermos Cup

Wei Liu,
Jin Li,
Hui Rong
et al.

Abstract: In product design, color is the first element that acts on the human visual senses and significantly influences consumer decisions. This study aimed to analyze consumers’ color preferences for products and explore the mathematical patterns of product color design. Firstly, sales data and images of popular thermos cups from Tmall and Jingdong (JD), two prominent e-commerce platforms in China, were obtained through data mining. Subsequently, this research focused on single-color thermos cups with high sales as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Lin et al (2019) studied Chinese consumers' attitudes towards using the O2O model for wooden furniture shopping and found variations in acceptance among consumers from different city tiers. Jiang et al (2020) and Liu et al (2024) found that color preferences have a significant impact on furniture choices. They also introduced a new color design practice method, offering important insights for the furniture industry.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al (2019) studied Chinese consumers' attitudes towards using the O2O model for wooden furniture shopping and found variations in acceptance among consumers from different city tiers. Jiang et al (2020) and Liu et al (2024) found that color preferences have a significant impact on furniture choices. They also introduced a new color design practice method, offering important insights for the furniture industry.…”
Section: Introductionmentioning
confidence: 99%